PRACTICING CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH TO IMPROVE STUDENTS’ READING COMPREHENSION IN RELATION TO MOTIVATION - Haerazi Haerazi; Zukhairatunniswah Prayati; Rully May Vikasari (University of Kuningan, 2019)
The need to acquire reading skills is increasing along with the needs of students to attain information. Therefore, this study aims at improving student’s reading comprehension viewed from the motivation level using the contextual teaching and learning (CTL) approach at SMPN 1 Jonggat. To this end, a classroom action research consisting of two cycles was applied. Each cycle consisted of four stages, namely plans, actions, observations, and reflections. The subject of this study was the second-grader of SMPN 1 Jonggat, while the object of this study was the use of contextual teaching and learning (CTL) approach to improve students’ reading comprehension in relation to motivation. The observation sheets, questionnaires, and reading tests were employed to collect the data. As result, the study showed that the use of CTL approach was effective to improve students’ reading comprehension and motivation to learn. Students’ achievement was 75 meaning that the passing grade enacted in the school was achieved. Meanwhile, the students’ motivation to learn was at the high level as proven by the percentage of students’ motivation which was at the standard value. Thus, it can be concluded that Contextual Teaching and Learning (CTL) approach can improve students’ motivation to learn as well as their reading comprehension.